PENGARUH JARAK TANAM DAN PUPUK NITROGEN TERHADAP PERTUMBUHAN DAN HASILTANAMAN WIJEN (SESAMUM INDICUM L.) VARIETAS SBR 1 - Purbosari, Purbosari; Faqih, Achmad; Jaenudin, Amran (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2023)
This research aims to determine the effect of the combination of spacing and nitrogen fertilizer on the growth and yield of sesame (Sesamum indicum L.), variety sbr 1. The research was carried out in Mekarjaya Village, Gantar District, Indramayu Regency - West Java. The experiment was carried out from August to December 2021. The location is situated at an altitude of 50 m above sea level (asl), the soil type is Latosol and Regosol association, including type D rain (slightly wet). The research method used is the research method with a randomized block design (RAK), the treatment consists of two factors which are repeated three times. The first factor is nitrogen fertilizer which consists of three levels, namely 100 kg/ha nitrogen fertilizer, 150 kg/ha nitrogen fertilizer, and 200 kg/ha nitrogen fertilizer. While the second factor is the spacing which consists of three levels, namely the spacing of 25 cm x 40 cm, the spacing of 25 cm x 50 cm, and the spacing of 25 cm x 60 cm. The main observation data were processed using linear model statistical tests, analysis of variance, and Scott-knot cluster further test analysis. To determine the correlation between the treatment with the growth component and the yield of the sesame, the correlation used is the Product Moment correlation coefficient. The research results showed: (1) The combination of spacing and nitrofen fertilizers had an effect on plant height at 28 DAP, stem diameter at 42 DAP, leaf area index at 42 DAP, plant growth rate at 42 DAP and seed weight per clump. effect on plant height at 14 DAP and 42 DAP, number of leaves at 14 DAP, 28 DAP and 42 DAP, stem diameter at 14 DAP and 28 DAP, root volume, leaf area index at 14 DAP and 28 DAP, plant growth rate at 14 DAP. DAP and 28 DAP, number of pods per cluster, number of pods per plot, weight of pods per cluster, weight of pods per plot, weight of 1000 seeds, and weight of seeds per plot, (2) The highest seed weight per plot was produced by the combination of treatment H, namely distance planting 25 cm x 60 cm and nitrogen fertilizer 150 kg/ha with an average weight of 0.711 kg (equivalent to 1.185 tons/ha), significantly different from other treatment combinations, (3) There was a significant correlation between plant height and number of leaver aged 28 DAP and 42 DAP with seed weight per plot in the medium and strong categories. However, there was no significant correlation between plant height and number of leaves aged 14 DAP with seed weight per plot in the medium category.